Therapeutic CD8 + T cell tissue retention and immunomodulation during ART interruption fail to prevent SIV rebound - M. Betina Pampena; Sadia Samer; Elise G. Viox; Kevin Nguyen; Claire Deleage; Leticia Kuri-Cervantes; James Regan; Vincent H. Wu; Steffen Docken; Jeffrey T. Safrit; Katharine J. Bar; Brandon F. Keele; et al. (Proceedings of the National Academy of Sciences, 2025)
A primary obstacle for HIV elimination is the long-term viral reservoir in lymphoid tissues (LT) that can cause rebound viremia if therapy is stopped. Cytotoxic CD8 + T cells are critical for control of HIV and Simian immunodeficiency virus (SIV) viremia; however, CD8 + T cells that migrate to LT are primarily noncytotoxic, calling into question whether these cells could reduce the viral reservoir on antiretroviral therapy (ART) or control viral replication when therapy is halted. To determine whether CD8 + T cells can inhibit viral replication when retained in LT, we inhibited lymphocyte egress from LTs in ART-treated SIV-infected rhesus macaques (RMs) during analytic treatment interruption (ATI) using the S1PR modulator FTY720 alone or in combination with anti-PD1 antibody (αPD1) and the IL-15 receptor superagonist N-803 to increase cytolytic function. FTY720 retained migrating CD4 + and CD8 + T cells in LT, whereas cytotoxic CD8 + T cells remained in the vasculature. After ATI and viral rebound, activated SIV-specific CD8 + T cells increased in frequency in LT of FTY720-treated RMs but failed to become cytotoxic or control plasma viremia compared to controls, even when combined with αPD1 and N-803. These findings indicate that LT-localized CD8 + T cells alone may be insufficient to delay or prevent plasma viral rebound during ATI.